2019
DOI: 10.3201/eid2507.181421
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Considerations for Movement Mapping to Identify Disease Transmission Hotspots

Abstract: Traditional public health methods for detecting infectious disease transmission, such as contact tracing and molecular epidemiology, are time-consuming and costly. Information and communication technologies, such as global positioning systems, smartphones, and mobile phones, offer opportunities for novel approaches to identifying transmission hotspots. However, mapping the movements of potentially infected persons comes with ethical challenges. During an interdisciplinary meeting of researchers, ethicists, dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Cross-national and national governance structures; institutional systems with regulatory, medical, ethical, and legal frameworks; and benchmarking standards have essential roles to play in the development and deployment of these new health technology systems. However, this review identified the urgent need for an ethical framework to underscore all AI-augmented infectious disease surveillance systems [ 18 , 19 , 30 ]. Considering the rapid development of global trade supply chains, mass gatherings, and international travel, World Health Organization’s International Health Regulations in 2005 [ 45 ] outlined the cross-border implications of a pandemic response and provided a framework for sharing, monitoring, and evaluating information from the sources of infections [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cross-national and national governance structures; institutional systems with regulatory, medical, ethical, and legal frameworks; and benchmarking standards have essential roles to play in the development and deployment of these new health technology systems. However, this review identified the urgent need for an ethical framework to underscore all AI-augmented infectious disease surveillance systems [ 18 , 19 , 30 ]. Considering the rapid development of global trade supply chains, mass gatherings, and international travel, World Health Organization’s International Health Regulations in 2005 [ 45 ] outlined the cross-border implications of a pandemic response and provided a framework for sharing, monitoring, and evaluating information from the sources of infections [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collecting personal mobility information, however, even for health application purposes, poses specific challenges when it comes to upholding ethical principles and issues of privacy [33] . Ultimately, the analysis of mobility data can be justified if it can yield benefits to public health.…”
Section: Related Workmentioning
confidence: 99%
“…The COVID-19 pandemic is worrisome because of the high morbidity and mortality rates in addition to the accompanying socio-economic and psychological burden. While the treatment and control of the disease decisions fall within the purview of policymakers and healthcare workers, the legal, cultural, socio-economic and psychological effects are issues that bother on the people [ 9 ]. Many of these issues have manifested in the last few weeks of implementing preventive measures for the pandemic, ranging from complaints about social distance, isolation, lockdown, testing, lack of basic amenities, especially water and electricity, contact tracing and data sharing.…”
Section: Commentarymentioning
confidence: 99%